What Is Korean Literature? - Kwŏn, Yŏng-min, 1948-; Fulton, Bruce (Book collections on Project MUSE., 2020)
"Outlining the major developments, characteristics, genres, and figures of the Korean literary tradition from earliest times into the new millennium, this volume includes examples, in English translation, of each of the genres and works by several of the major figures discussed in the text, as well as suggestions for further reading"--